Early Historical Atlas Depictions of Agriculture in Kansas: 1880s-Early 1900s - Hayes, Kasey (Kansas State University, The Chapman Center for Rural Studies, 2012)
My research project is over early historical depictions of agriculture in Kansas 1887. I am trying to figure out if farms in the historical atlas of Kansas truly represented agriculture; did the farmsteads, livestock, and crops really look like the pictures? This study is includes a focus on Pottawatomie County, Kansas, pictures from the 1887 historical atlas, actual photographs of Kansas agriculture, a brief historical background on agriculture in general, and information from the First Biennial Report of the State Board of Agriculture Kansas.
Kasey Hayes, “Early Historical Atlas Depictions of Agriculture in Kansas: 1880s-Early 1900s,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/222.
Keywords: 1187 Official Atlas of Kansas; Cadestral map; cartography; lithographs; Pottawatomie County; Union Atlas Company